Computers, cockroaches, and ecosystems : understanding learning through metaphor - Pugh, Kevin J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Of all the topics ever studied, surely one of the most compelling is human learning itself. What is the nature of the human mind? How do we understand and process new information? Where do new ideas come from? How is our very intelligence a product of society and culture?Computers, Cockroaches, and Ecosystems: Understanding Learning through Metaphor brings to light the great discoveries about human learning by illuminating key metaphors underlying the major learning perspectives. Such metaphors include, among others, the mind as computer, the mind as ecosystem, and the mind as cultural tools. These metaphors reveal the essence of different learning perspectives in a way that is accessible and engaging for teachers and students. Each metaphor is brought to life through stories ranging from the humorous to the profound.The book conveys scholarly ideas in a personal manner and will be a delight for teachers, university students, parents, business or military trainers, or anyone with an interest in learning.